All Days 2009
DOI: 10.2523/iptc-13732-ms
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Fuzzy Logic and Artificial Neural Networks for building a Hydraulic Unit-Based Model for Permeability Prediction of a Heterogeneous Carbonate Reservoir

Abstract: TX 75083-3836, U.S.A., fax +1-972-952-9435. AbstractPermeability is one of the crucial parameters in dynamic reservoir modeling and simulation. Direct measurement of permeability through coring and wireline formation testing is expensive and sometimes hard to achieve. In addition, the interval of coring is always limited. In this study available core and wireline log data of a heterogeneous carbonate reservoir located in sarvak formation of Iran are used to predict permeability not only for the cored but un-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In view of the above, combining the limitations of GA, ANN, and fuzzy logic in a hybrid model could only result in a combined overall inefficiency despite their reported good individual performances (Xie et al 2005;Mohsen et al 2007;Ali et al 2008;Zarei et al 2008;Al-Anazi et al 2009;Shahvar et al 2009;Park et al 2010a). Various studies to address these reported problems of ANN through the development of other algorithms such as cascade correlation and radial basis function did not improve its overall performance (Bruen and Yang 2005).…”
Section: Hybrid Intelligent Systems In Petroleum Reservoir Characterimentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the above, combining the limitations of GA, ANN, and fuzzy logic in a hybrid model could only result in a combined overall inefficiency despite their reported good individual performances (Xie et al 2005;Mohsen et al 2007;Ali et al 2008;Zarei et al 2008;Al-Anazi et al 2009;Shahvar et al 2009;Park et al 2010a). Various studies to address these reported problems of ANN through the development of other algorithms such as cascade correlation and radial basis function did not improve its overall performance (Bruen and Yang 2005).…”
Section: Hybrid Intelligent Systems In Petroleum Reservoir Characterimentioning
confidence: 99%
“…In the spirit of pseudo-hybridization, Shahvar et al (2009) used fuzzy logic to predict the flow zone index (FZI) of reservoir rocks from wireline logs which served as part of the input for an ANN model for the estimation of permeability. They reported that with the successful prediction of FZI, the result of the permeability estimation was highly satisfactory and more robust when compared with the conventional multi-linear regression.…”
Section: Hybrid Intelligent Systems In Petroleum Reservoir Characterimentioning
confidence: 99%
“…Many operators agree that the candidate well choosing process involves a high level of uncertainty and ambiguity [7,21]. Large scale field applications also show that one main factor leading to prominent dissatisfaction is the systems' inability to handle uncertainty [23,27].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these approaches carries with it a set of advantages and limitations. Hence, it would seem natural that some attempts have been made to integrate them in order to obtain the best of all approaches [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, several researchers have investigated the individual applicability of these tools to geosciences-related problems [10][11][12][13][14][15][16]. This study comprises two major parts.…”
Section: Introductionmentioning
confidence: 99%